Pendampingan Renovasi Minaret Masjid Al-Mizan - Farida Ayu Avicena Nusantari; Inggit Musdinar Sayekti Sihing Yang Mawantu (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Assistance activities were carried out at the Al-Mizan Mosque which is located in Rawamangun Village, Pulo Gadung District, East Jakarta City. Until now, the Al-Mizan Mosque has not been equipped with a minaret in which there is a complete sound system. There is already a sound system room but only in the form of a room on the 2nd floor, to be precise, above the ablution room. This condition causes the sound range of the call to prayer from the Al-Mizan Mosque to be less than optimal. The sound system room which is equipped with loudspeakers is currently only 7.2 meters high from the floor of the mosque. Even though many residential buildings around the Al-Mizan Mosque are higher than the loudspeaker point. To overcome this problem, the management of the Al-Mizan Mosque wants to build a Minaret. Based on these conditions, the Architecture Study Program at Budi Luhur University held Community Service activities to design and make plans to As-Built Drawings for the Minaret of the Al-Mizan Mosque, using knowledge from the fields of architecture and economics to control the use of renovation funds. The design of the minaret of the Al-Mizan Mosque was adjusted to input from the mosque manager and adapted to architectural standards, while the as built drawing of the mosque's minaret was adjusted to what was built in the field. The purpose of adding the minaret to the mosque is for the mosque to have a minaret as a good loudspeaker with a wider range than before and supported by an adequate sound system, thereby providing added value to the congregation of the mosque.